Corporate Social Responsibility and Corporate Values: The Moderating Role of Leverage and Company Size - Abdul Malik Kumar; Sunaryati Hardiani; Chodidjah Chodidjah (Jurnal Manajemen dan Kewirausahaan, 2022)
The purpose of this study is to prove the moderating role of leverage and firm size on the CSR relationship with manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Purposive sampling used resulted in 82 companies. This data analysis method uses Moderated Regression Analysis (MRA) through ordinary least squares (OLS) in stages to see the moderating function of leverage and firm size. The results of the study prove that leverage plays a role in moderating the negative effect of CSR on firm value. Meanwhile, firm size is not proven to moderate the relationship between CSR and firm value.